Minimal Complexity C-complexes for Colored Links - Roth, Grant (My University, 2015)
In this project, we study the analogous measure of complexity given by a generalization of a surface called a C-complex.
Color poster with text and images.
Keywords: C-complex; Links; Mathematics; Posters